Stalingrad Tractor Factory - Jeremy Younkin:::Creator::::::::::::
The front of Stalingrad Traktornaiy Zavod Imeni F. E. Dzerzhinskogo (Stalingrad Tractor Factory), which John Steinbeck and Robert Capa visited. In this photo it is called the Volgograd Traktornaiy Zavod Imeni F. E. Dzerzhinskogo. This factory played a vital role in the defense of the city during the Battle of Stalingrad, continuing to produce t-34 tanks throughout the battle.